Risk stratification and mortality prediction in Falciparum Malaria - Khadanga, Sagar (International Journal of Medical Research and Review, 2014)
Falciparum malaria has remained an important public health problem in India over the years. WHO enumerates a list of complications to diagnose severe falciparum malaria which was initially provided in 1990 and then revised in 2000. But the importance and prognosis of each complication has not been assigned. Various strategies have been employed for risk stratification in falciparum malaria by various authors in different parts of world. Here we would like to discuss the available literatures from India and some accomplished western literatures to prognosticate severe falciparum malaria patients.